Development of Digital Marketing Utilization Based on Analysis of Digital Marketing Implementation in the Marketing Strategy of X Hospital Mojokerto - Tumbelaka, Reyner Valiant; Chalidyanto, Djazuly; Purnomo, Windhu (Universitas Muhammadiyah Surabaya, 2025)
This study focuses on assessing the effectiveness of digital marketing applications at X Hospital Mojokerto by reviewing patient demographics, online behavior, and perceptions of digital media. A quantitative approach using a survey method was used, with a questionnaire consisting of several questions, to collect data from new patients who access health information through the hospital's digital media. The results indicate that patients aged 26–35 years dominate, and TikTok and Instagram are shown as the primary platforms used for accessing health information. Nonetheless, only Facebook indicated a statistically meaningful result on patients' choices in seeking hospital care. The remaining variables, such as demographic factors and digital media perception, demonstrated no significant impact. The study implies that digital platforms' usage behavior and content strategy bring a greater impact than demographic characteristics. Recommendations cover maximizing Facebook performance, improving content interaction on Instagram and TikTok, and implementing communication strategies tailored to user behavior to strengthen communication outcomes and conversion.